Fisherman’s Willingness to Pay for Sustainable Lagoon Ecosystem Management: A Locality Study in Jaffna Lagoon of Sri Lanka - Krishnapillai, S.; Sarujan, S.; Sivashankar, S. (World Scientific Publishing Europe Ltd, 2022)
This study estimates willingness to pay (WTP) for different sustainable ecosystem management measures in the Jaffna lagoon. For this study, 118 fishermen were randomly selected along the lagoon. Choice modelling approach was employed and a conditional logit model was developed. This study found that fishermen from village communities are willing to pay more for increasing the number of mangroves and improving tourist facilities. The availability of land for planting mangroves and improving tourist facilities and increasing income from other sources positively influence the fisherman’s WTP for sustainable ecosystem management. Establishing fishing harbour facilities, properly planned multi-storey housing units in town areas would increase fishermen’s support for planting mangroves and developing tourist spots. Increasing income from other sources and fishermen’s awareness on the impact of inappropriate fishing gears and enforcing mechanism would increase fishermen’s support to ban the inappropriate fishing gears. Based on this study, government authority could make appropriate policy for urban and village coastal lagoon ecosystem management.
Keywords: Choice modelling; Conditional logit model; Sustainable lagoon ecosystem management